Producing Just Enough Documentation: An Optimization Approach Applied to the Software Architecture Domain - Diaz Pace, Jorge Andres (2016)
The Software Architecture is an important asset in a software development process, which serves to share and discuss the main design concerns among the project stakeholders. The architecture must be properly documented (e.g., via a Wiki environment) to be effectively used by these stakeholders. However, the process of producing architecture documentation often fails to deliver contents that address the stakeholders’ information needs. To address the problem, we argue for a knowledge management strategy in which: (i) architecture documentation is created incrementally; and (ii) its contents are driven by a model of stakeholder preferences. In this work, we present an information optimization approach applied to the architecture documentation domain, derived from an existing documentation method called Views & Beyond. To do so, we define the Next SAD Version Problem (NSVP) and then provide tool support to assist architects in producing cost-effective documentation. Based on prior work, we perform a sensitivity analysis of the optimization model and develop a robust formulation that takes into account uncertainty in the parameter estimations for NSVP instances, thus improving the outcomes of our documentation assistant.